The Concept of Calm Soul in The Qur’an - Marno; Marhamah (Syntax Corporation Indonesia, 2021)
This study aims to discover the influence of a calm soul to human life through Allah’s guidance and to take the lessons from Quranic verses about a calm soul. The method of study is descriptive qualitative with the library research (literature) which is compiled by the concept of Tafsir Maudhu’i. The results of this study show that muthmainnah verses more revealed after the prophet migrated (hijrah). According to the word of muthmainnahin the Quran that related to the Nasr Hamid’s idea in the pre-emigration phase, it is focused on the understanding or depiction of muthmainnah and its characteristics are that the quiet soul is the soul that returns to its blessed and blessed God, the soul that belongs to the servant of God and will enter heaven. Whereas the post-hijrah period, which contains in the muthmainnah word is more focused on the application of muthmainnah in dealing with various problems.